Air power a global history - Black, Jeremy (Rowman & Littlefield Publishers, 2016)
Jeremy Black, one of the world's finest scholars of military history, provides a lucid analysis of the use of airpower over land and sea both during the two world wars and the more limited wars of the twentieth and twenty-first centuries. Considering both the theory and praxis of air power, the author begins with hot air balloons, and then highlights the use of zeppelins, piston engine fighters, jet bombers, and finally the so-called Military Revolution of today.